Performance Appraisal in Public Sector Banks-A Case of The State Bank of India - Nandan, Shefali (Gyan Management Journal, 2007)
Ever since the economic reform were initiated in India, Indian organisations have been revamping thei tern to cope with th increasing competition. Thi has been true for public a well a pri ate ector enterprise .Organizti ns today are characterized by:uslomer focus, quick response, emphasi on teamwork and innovation Human Re. ource ystem. · have been re-designed to increase the effectvene and efficiency 0f employees and also to attract and =-